Collinear Acousto-Optic Filtration With Electronically Adjustable Transmission Function - Sergey N. Mantsevich; Vladimir I. Balakshy (IEEE Photonics Journal)
An acousto-optic system containing collinear acousto-optic filter fabricated from calcium molybdate crystal and a positive electronic feedback was examined. The feedback signal is formed due to the optical heterodyning effect that appears for the special geometry of polarizer and analyzer polarization planes mutual orientation between which the collinear filter is located. It is shown that the feedback circuit electrical parameters variation enable controlling the spectral characteristics of the acousto-optic collinear filtration, resulting in enhancing the maximal spectral resolution and transmission function side lobes suppression.